The role of intrinsic motivation in sustaining citizen science participation among diverse participants in a corporate volunteer program - Bradley C. Allf; Lincoln R. Larson (PLoS ONE, 2025)
Citizen science enables volunteers from the public to contribute to scientific research. While citizen science may be an avenue for “democratizing” science and facilitating learning among volunteers, projects tend to attract homogeneous volunteers already highly engaged in science. The emergence of facilitator organizations such as schools, churches and corporations, that connect existing volunteer-oriented groups with citizen science, offers a potentially viable avenue through which to attract more diverse volunteers, with more to gain from their experience. However, attracting and retaining these volunteers requires a detailed understanding of their motivations, and how different types of motivations might facilitate sustained, impactful experiences. The objective of this study was to evaluate the motivations, engagement, and diversity of citizen science volunteers recruited through a corporate volunteer program. We assessed these outcomes using digital participation metadata and a survey of 388 employee volunteers. Over the course of three years (2019–2022), this program enabled over 13,000 volunteers to contribute approximately 31,000 hours to 49 citizen science projects, though approximately half of volunteers participated only once. Survey results indicated that most volunteers (85%) were new to citizen science, and were more representative of the general US population in terms of their race/ethnicity, gender and educational attainment than typical citizen scientists. Volunteers’ motivations were primarily self-determined (i.e., intrinsic). Less self-determined (i.e., extrinsic) motivations, like a sense of obligation or group pressure, were linked to lower levels of participation in the program. In addition, socio-demographic factors (race/ethnicity and age) were associated with differing levels of participation. In conclusion, volunteers from facilitator organizations can make significant contributions to citizen science and reshape citizen science into a more diverse and inclusive pursuit. However, sustained engagement by these volunteers relies in part on volunteers participating for intrinsic reasons. To facilitate self-determined motivation, projects should meet volunteers’ needs for competence, relatedness and autonomy.